(untitled) (Research, Society and Development, 2024)
Introduction: Violence against women is a public health issue and a serious social problem that affects the physical, emotional, and social integrity of victims. In addressing this issue, nurses are on the front lines of caring for women in vulnerable situations. Objective: Highlighting the role of nurses in identifying and welcoming women who are victims of violence emphasizes the importance of emotional support and referral to support networks. Methodology: The methodology of this article is based on a bibliographic review of research and articles published on recognized sites and databases, such as SciELO, Lilacs, and other relevant academic sources. Studies published over the last ten years were selected to ensure the relevance and currency of the content. Conclusion: It is concluded that nursing plays a crucial role in the fight against gender-based violence, both through direct contact with the victim and through its involvement at various levels of prevention and intervention. In healthcare settings and consultations, nurses have a unique opportunity to identify subtle signs of violence, such as anxious behaviors, bruises, or vague descriptions of recurring injuries.